Unveiling Authentic Leadership: A Comprehensive Literature Review - Mengmeng, Li; Aziz, Nor Azni Abdul; Omar, Muhd Khaizer (Journal of Ecohumanism, 2024)
Leadership theory has always been a hot topic in global leadership research. In today's situation where moral crises, malfeasance, and slack management behaviors occur frequently, authentic leadership, as an emerging leadership style, combines the positive factors of various leadership styles and is considered to be a reflection of the regression of properties and process for eternal, true, and basic leadership. This study conducted a relatively systematic review and review of relevant domestic and foreign literature from the aspects of the concept, measurement, and mechanism of authentic leadership, in order to grasp the latest trends and lay the foundation for future related research.